Iron and virulence in Stenotrophomonas maltophilia: all we know so far - V., Kalidasan; Joseph, Narcisse; Kumar, Suresh; Awang Hamat, Rukman; Neela, Vasantha Kumari (Frontiers Research Foundation, 2018)
Stenotrophomonas maltophilia is a multi-drug-resistant global opportunistic nosocomial pathogen, which possesses a huge number of virulence factors and antibiotics resistance characteristics. Iron has a crucial contribution toward growth and development, cell growth and proliferation, and pathogenicity. The bacterium found to acquire iron for its cellular process through the expression of two iron acquisition systems. Two distinct pathways for iron acquisition are encoded by the S. maltophilia genome-a siderophore-and heme-mediated iron uptake system. The entAFDBEC operon directs the production of the enterobactin siderophore of catecholate in nature, while heme uptake relies on hgbBC and potentially hmuRSTUV operon. Fur and sigma factors are regulators of S. maltophilia under iron-limited condition. Iron potentially act as a signal which plays an important role in biofilm formation, extracellular polymeric substances (EPS), extracellular enzymes production, oxidative stress response, diffusible signal factor (DSF) and siderophore production in S. maltophilia. This review summarizes the current knowledge of iron acquisition in S. maltophilia and the critical role of iron in relation to its pathogenicity.